The Role of Society in Preventing Premarriage Sexual Behavior - Wahyuningsih Wahyuningsih (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
Background: Adolescents are one of the population groups that are easily affected by the flow of information, both negative and positive. One impact of the negative flow of information is premarital sexual behavior in adolescents. In fact, teens are expected to be able to replace the previous generation with optimal performance quality in accordance with their growth and development related to adolescent reproductive health rights. In this case, there needs to be efforts made by the community around adolescents in the prevention of premarital sexual behavior . Objectives: To describe the role of the community in preventing premarriage pregnancy to adolescents in the village of Trirenggo, BantulResearch Methodology: This research uses quantitative and qualitative research methods with a phenomenological approach. The sampling technique uses purposive sampling . The study was conducted in June-August 2019 in Trirenggo, Bantul. The research instrument used a questionnaire and interview guidelines compiled by the researcher. The data analysis process in this study uses the frequency distribution for quantitative research and steps from Colaizzi for qualitative research.The results of the study: (1) Community norms already exist in Trirenggo, Bantul, but the implementation is still not optimal (2) Social control has been carried out by the Trirenggo community but it is still not well targeted in its implementation .Conclusion: Community norms still do not function in the prevention of premarriage pregnancy, as well as the minimum community participation in social control.